Cannabidiol nanoemulsion for eye treatment - Anti-inflammatory, wound healing activity and its bioavailability using in vitro human corneal substitute - Tran, Van Nguyen; Strnad, Ondřej; Šuman, Jáchym; Veverková, Tereza; Sukupová, Adéla; Cejnar, Pavel; Hynek, Radovan; Kronusová, Olga; Šach, Josef; Kaštánek, Petr; Ruml, Tomáš; Viktorová, Jitka (International journal of pharmaceutics, 2023)
Cannabidiol (CBD) is the non-psychoactive component of the plant Cannabis sativa (L.) that has great anti-inflammatory benefits and wound healing effects. However, its high lipophilicity, chemical instability, and extensive metabolism impair its bioavailability and clinical use. Here, we report on the preparation of a human cornea substitute in vitro and validate this substitute for the evaluation of drug penetration. CBD nanoemulsion was developed and evaluated for stability and biological activity. The physicochemical properties of CBD nanoemulsion were maintained during storage for 90 days under room conditions. In the scratch assay, nanoformulation showed significantly ameliorated wound closure rates compared to the control and pure CBD. Due to the lower cytotoxicity of nanoformulated CBD, a higher anti-inflammatory activity was demonstrated. Neither nanoemulsion nor pure CBD can penetrate the cornea after the four-hour apical treatment. For nanoemulsion, 94 % of the initial amount of CBD remained in the apical compartment while only 54 % of the original amount of pure CBD was detected in the apical medium, and 7 % in the cornea, the rest was most likely metabolized. In summary, the nanoemulsion developed in this study enhanced the stability and biological activity of CBD.
Keywords: antiflogistika; rohovka; Cornea; Humans; lidé; Cannabidiol; kanabidiol; Anti-Inflammatory Agents; biologická dostupnost; Wound Healing; hojení ran; Biological Availability